Utilization Of Moringa Leaves As A Nutrient to Prevent Stunting In Children In Gantiang Village, Padang Panjang City - Meri Susanti; Annisa Fauzana; Yoneta Srangenge; Nova Syafni; Najmiatul Fitria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Stunting is a critical public health issue in Indonesia. Despite various nutrition programs, the utilization of nutritious local foods, such as Moringa oleifera leaves, has not been maximized due to limited public awareness and inadequate education. This activity aims to increase public knowledge of the nutritional content and benefits of Moringa leaves for preventing stunting, and to provide training in processing Moringa into healthy foods. Methods: The activity was conducted on October 4, 2025, in Gantiang Village, Padang Panjang City. The target group comprised housewives, health care workers, and caregivers of toddlers. Data were collected through pre- and post-tests, as well as surveys of participant satisfaction and interest. Results: Following the educational and processing demonstration, participants' knowledge increased significantly; the program was deemed highly beneficial, and most expressed interest in incorporating Moringa leaf preparations into their family menus. Conclusion: Education and training in Moringa leaf processing have been effective in increasing public knowledge and interest in using Moringa as a nutritious food, thereby potentially supporting efforts to prevent stunting. For sustainability, it is recommended that this program be integrated into integrated health posts (Posyandu) and that further training be conducted to ensure that Moringa leaf consumption becomes a regular part of family eating habits.